Leisure participation and mental health among middle-aged and older adults with physical disabilities: a systematic review - Kim, Sohyun Angela; Yoo, Madelyn; Martin, Noah; Stark, Susan; Devine, Megen; Chen, Szu-Wei (Disability and rehabilitation, 2025)
To examine the effects of leisure participation on mental health for middle-aged and older adults with physical disabilities. A systematic review conducted in March-May 2022 with an updated search in February 2024 retrieved data from MEDLINE, CINAHL, PsycInfo, and EMBASE. Inclusion criteria included a study population with a mean age ≥45 years and with physical disability, and original, peer-reviewed literature. Exclusion criteria included non-community-dwelling participants, participants outside the specified age range, review studies, intervention studies not focused on leisure or intrinsically motivated activities, and studies without full text. The Oxford 2011 Levels of Evidence, NIH study quality assessment tool, and Cochrane ROBINS-I tools were used to assess the evidence strength and the risk of bias. A data extraction table was created to analyze and synthesize the results. Eleven articles with 18,681 total participants were thoroughly reviewed. Most studies were longitudinal survey, cohort, and cross-sectional studies. Evidence indicates that leisure participation benefits mental health (depression, anxiety, happiness, and well-being) and other health-related outcomes. Findings should be interpreted with caution due to lack of high-level evidence. Future research should consider alternative study designs in addition to RCTs to better capture the individualized nature of leisure activities.